Preterm Pulmonary Hemorrhage Is Associated with Multiple Births but Not with Intracytoplasmic Sperm Injection: A Cohort Study on Medical Records - Stierling, Stefanie; Hilgers, Ralf-Dieter; Trepels-Kottek, Sonja; Heimann, Konrad; Orlikowsky, Thorsten; Schoberer, Mark (American Journal of Perinatology, 2018)
Objective Pulmonary hemorrhage (PH) is a severe complication in preterm neonates. This study aims to identify risk factors and comorbidities of PH.Study Design A single-center cohort study on medical records including all preterm neonates of <30 weeks' gestational age was conducted in the neonatal intensive care unit of Universitätsklinikum Aachen, Germany. The occurrence of PH served as a primary end point. Gestational age, birthweight, sex, multiple births, intracytoplasmic sperm injection (ICSI), intubation, surfactant, antenatal steroids, intraventricular hemorrhage (IVH), amniotic infection syndrome, and persistent ductus arteriosus were studied as risk factors.Results In this study, 344 preterm neonates were included, of whom 36 suffered from PH (10.5%). The mean time of the first occurrence was the third day of life (standard deviation [SD]: 1.2). On average, the patients suffered from 1.5 incidents (SD: 0.8) of PH, of whom 50% were severe. Preterm neonates born as multiples (95% confidence interval [CI]: 3.1, 26.9) and those who suffered from IVH (95% CI: 2.7, 18.9) had a significantly increased risk of PH. ICSI was not an independent risk factor.Conclusion PH is significantly associated with IVH and multiple births but not with ICSI. The identification of patients at risk allows to apply prophylactic strategies of ventilation and pharmacological treatment.
Keywords: pulmonary hemorrhage; preterm; neonate; multiple births; intraventricular hemorrhage; intracytoplasmic sperm injection; in vitro fertilization